1978
DOI: 10.1126/science.99814
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Experimental Monkeys Against Plasmodium falciparum : A Possible Safe Adjuvant

Abstract: Owl monkeys (Aotus trivirgatus griseimembra) were effectively immunized against a human malaria parasite, Plasmodium falciparum. Two injections of antigen, primarily mature segmenters with fully developed merozoites, mixed with adjuvant (6-O-stearoyl-N-acetylmuramyl-L-alanyl-D-isoglutamine and liposomes) were administered intramuscularly at a 4-week interval. Approximately 2 weeks after the second vaccination, the monkeys were challenged with the homologous strain of P. falciparum. All immunized monkeys surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…Administered in an aqueous medium certain lipophilic derivatives of MDP have been shown capable of enhancing the cell-mediated immune response (44,47) whereas MDP and most of its analogues enhance humoral antibody production. Such an adjuvant activity has been demonstrated with classical laboratory antigens, but also with conventional vaccines against viral, bacterial, or parasitic pathogens (4,45) or with several synthetic antigens which copy epitopes of these pathogens (31,36,3,5). Anti-hormone vaccines have also been produced using as antigens the terminal fragment of .a-HCG or a hypothalamic peptide, LH-RH (for luteinizing hormone-releasing hormone) (6).…”
Section: A) Adjuvant Activitymentioning
confidence: 99%
“…Administered in an aqueous medium certain lipophilic derivatives of MDP have been shown capable of enhancing the cell-mediated immune response (44,47) whereas MDP and most of its analogues enhance humoral antibody production. Such an adjuvant activity has been demonstrated with classical laboratory antigens, but also with conventional vaccines against viral, bacterial, or parasitic pathogens (4,45) or with several synthetic antigens which copy epitopes of these pathogens (31,36,3,5). Anti-hormone vaccines have also been produced using as antigens the terminal fragment of .a-HCG or a hypothalamic peptide, LH-RH (for luteinizing hormone-releasing hormone) (6).…”
Section: A) Adjuvant Activitymentioning
confidence: 99%
“…Successful experimental vaccinations with erythrocytic stages of malaria parasites have indicated that merozoites and schizonts are the best sources of antigens that elicit a protective immune response (1)(2)(3). Identification of these stage-specific functional antigens would provide a rational basis for developing a malaria vaccine suitable for humans.…”
mentioning
confidence: 99%
“…Aotus monkeys, which are susceptible to infection with P. falciparum (8,9,17,27,34,35,39,41,(44)(45)(46)(47)58) without prior splenectomy (48), are a World Health Organizationrecommended model to test the efficacy of malaria blood stage vaccine candidates. An evaluation of the protective potential of a series of peptide sequences derived from proteins isolated from P. falciparum-infected erythrocytes in the Aotus infection model identified the partially protective peptides 35.1, 55.1, and 83.1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric SPf66 (SPf66 pol ) (CDELEAETQNVYAAPNANPYSLFQKEKMV LPNANPPANKKNAGC), monomeric SPf66 (SPf66 mon ) without the terminal cysteines of the SPf66 pol peptide, and the polymeric SPf66 building blocks 35.1 pol (CYGGPANKKNAGC), 55.1 pol (CGDELEAETQNVYAAGC), and 83.1 pol (CGYSLFQKEKMVLGC) were a kind gift of M. E. Patarroyo. 35.1 mon (YGG PANKKNAG) and RAP-1 [47][48][49][50][51][52][53][54][55][56][57] (YWTPINKKEFL) were obtained from SigmaGenosys.…”
Section: Methodsmentioning
confidence: 99%